Construction delays understanding them clearly, analyzing them correctly - Trauner, Theodore J. (Elsevier ; Butterworth-Heinemann, 2009)
Delays in construction projects are frequently expensive, since there is usually a construction loan involved which charges interest, management staff dedicated to the project whose costs are time dependent, and ongoing inflation in wage and material prices. Many techniques are used to analyze delays. Some of these methods have inherent weaknesses and should be avoided. This book points out the shortcomings of these faulty methods and explains how a delay analysis should be performed. It then describes specifically how the analysis is done with CPM schedules. A explanation of delays and delay.
Previous edition: Construction delays : documenting causes, winning claims, recovering costs / Theodore J. Trauner, Jr.
Additional authors: William A. Manginelli, J. Scott Lowe, Mark F. Nagata, Brian J. Furniss.
Includes index.
Keywords: Construction industry -- Management.; Production scheduling.; Construction projects.; elektronické knihy; electronic books